10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background Children with dyslexia are at elevated risk of mental health difficulties, both internalizing (emotional) and externalizing (behavioural) problems. Clever Kids is a nine-week socio-emotional well-being programme developed specifically to support upper primary school children with dyslexia. Aims We conducted a pre-registered randomized-controlled trial to test the efficacy of Clever Kids. Method Seventy-eight children (M age = 10.19 years, 54% female) with clinically diagnosed dyslexia took part in the trial. Children were randomized to either attend Clever Kids (n = 38) or to a wait-list control condition (n = 40). Coping skills, emotion regulation, self-esteem, perseverance, assertiveness, as well as mental health (internalizing and externalizing symptoms) were measured at pre-programme, post-programme and at three-month follow-up using well-validated measures. Results The predicted interactions between intervention condition and time were significant for six outcomes. Attending Clever Kids was associated with significant improvements in child-reported coping, emotion regulation, academic and social self-esteem, as well as parent-reported anxiety and depression. Effects were all maintained at three-month follow-up. Unexpectedly, being assigned to the wait-list condition was associated with improvements in perseverance at follow-up assessment. For all other outcomes, interactions between intervention condition and time were non-significant. Conclusion Clever Kids appears to be a promising programme for supporting socio-emotional well-being of children with dyslexia. Future research should consider incorporating caregivers more explicitly into the programme and alternative delivery modes, which could expand the reach of the programme.